(untitled) (Research, Society and Development, 2021)
It is estimated that 200 million children of preschool age worldwide are affected by enteroparasites, mainly due to the lack of strategies to improve the population’s socioeconomic level, therefore, the objective of this work was to carry out a review of cases of parasitic infections in preschool children in Brazil. To carry out the work, a bibliographic survey was made through electronic consultation in the Scielo database, Google academic, PubMed and CAPES. The analyzed studies showed that the most diagnosed parasites were Ascaris lumbricoides, Giardia lamblia and Entamoeba histolytica in the child population. In the absence of initial symptoms, diagnosis becomes difficult, but long-term damage to the body has manifested itself at some point, such as anemia, apathy, fatigue, excessive sleepiness, irritability, among others, making routine examinations necessary. The parasitological examination of feces, which is of fundamental importance in the identification of the parasite and also for the correct use of the drug, once it is specific to each parasitosis. The indiscriminate use of anthelmintics without laboratory diagnosis can develop drug resistance, in addition to causing a secondary or adverse problem due to unnecessary exposure to the drug. In view of the above, it is concluded the health education measures carried out by teachers and parents is one of the main measures to prevent contamination by intestinal parasites in children. More information and work involving children, parents and teachers is necessary in order to educate against infection by human parasites.